Sixth international conference on AIDS : San Fransisco, California, USA : final program and abstracts : wednesday 20 june 1990 - thursday 21 june 1990. (San Francisco, 1990)
Fonds Suzan Daniel (FSD)
Bestaat uit 3 delen
Meerdelige publicatie
Keywords: 1990 - 1990.; conferenties; aids